The Emperor’s New Clothes: Maclean’s, NSSE, and the Inappropriate Ranking of Canadian Universities - Grayson, J Paul (Canadian Journal of Higher Education, 2020)
Most Canadian universities participate in the US-based National Survey of Student Engagement (NSSE) that measures various aspects of “student engagement.” The higher the level of engagement, the greater the probability of positive outcomes and the better the quality of the school. Maclean’s magazine publishes some of the results of these surveys. Institutions are ranked in terms of their scores on 10 engagement categories and four outcomes. The outcomes considered are how students in the first and senior years evaluate their overall experiences (satisfaction) and whether or not students would return to their campuses. Universities frequently use their scores on measures reported by Maclean’s in a self-Congratulatory way. In this article, I deal with levels of satisfaction provided by Maclean’s. Based on multiple regression, I show that of the 10 engagement variables regarded as important by NSSE, at the institutional level, only one explains most of the variance in first-year student satisfaction. The others are of limited consequence. I also demonstrate, via a cluster analysis, that, rather than there being a hierarchy of Canadian institutions as suggested by the way in which Maclean’s presents NSSE findings, Canadian universities can most adequately be divided into a limited number of different satisfaction clusters. Findings such as these might serve as a caution to parents and students who consider Maclean’s satisfaction rankings when assessing the merits of different universities. Overall, in terms of first-year satisfaction, the findings suggest more similarities than differences between and among Canadian universities.